MicroRNA-203 Acts as a Potent Suppressor in Septic Shock by Alleviating Lung Injury via Inhibition of VNN1 - Lan Ling; Hai-Tao Lu; Hai-Feng Wang; Mei-Jia Shen; Hong-Bo Zhang (Karger Publishers, 2019)
Background: Septic shock, the most serious complication of sepsis, is a life-threatening disease that is mainly characterized by hypoperfusion and multiple organ failure. Various aberrantly expressed microRNAs (miRNAs) have been reported to be related to septic shock. We explored the regulatory effect of microRNA-203 (miR-203) on lung injury in septic shock mice. Methods: Microarray-based gene expression profiling related to septic shock identified the differentially expressed gene vanin-1 (VNN1) and potential regulatory miR-203. miR-203 was predicted to mediate VNN1 expression, thus affecting septic shock, which was investigated by treatment with miR-203 mimic, miR-203 inhibitor, and siRNA-VNN1 in septic shock mouse models. Polymorphonuclear neutrophils (PMNs) and pulmonary alveolar macrophages in bronchoalveolar lavage fluid (BALF) as well as the wet/dry ratio of the lung were also measured to assess lung injury. Additionally, the effects of miR-203 on inflammatory cytokines, oxidative stress indexes, blood biochemical indexes, serine-threonine protein kinase (AKT) signaling pathway-related factors, and apoptosis-related factors were determined. Results: VNN1 was verified to be targeted and negatively regulated by miR-203. In mouse models of septic shock, weak expression of miR-203, high expression of VNN1, and inhibition of AKT signaling pathway were identified. In response to miR-203 mimic and VNN1 gene silencing, mouse models of septic shock displayed reduced apoptosis, MDA, ALT, and AST in lung tissues, decreased levels of TNF-α, IL-1β, IFN-γ, IL-10, and IL-6, in serum, and reduced PMN and PAM levels in BALF, in addition to elevated SOD activity. Notably, the presence of miR-203 mimic led to AKT signaling pathway activation. Conclusion:This study shows that upregulating miR-203 can alleviate lung injury through activation of the AKT signaling pathway by downregulating VNN1 in septic shock.